Potential of Endophyctic Fungi Isolates IFAZ-6 from Bidara Root (Ziziphus mauritiana Lam.) as Antibacterials Againts Digestive Tract Infection - janna, Nur; Fitriana, Fitriana; Amirah, Sitti (Fakultas Farmasi, Universitas Muslim Indonesia, 2024)
Bidara root (Ziziphus mauritiana Lam.) has activity as an antibacterial against digestive tract infections. This study aims to determine the antibacterial activity of isolate IFAZ-6 endophytic fungi of bidara root against bacteria that cause digestive tract infections using the TLC-Bioautography method. Purification was conducted on the active isolate IFAZ-6 to obtain a pure endophytic fungi isolate. Subsequently, macroscopic and microscopic observations were carried out. Then, fermentation was performed in MYB (Maltose Yeast Broth) medium for 21 days. Screening and evaporation were conducted to produce an extract. The obtained extract was subjected to TLC analysis using a chloroform: methanol eluent (7:1). The TLC-Bioautography test was conducted against Escherichia coli, Salmonella typhi, Shigella dysentriae, and Vibrio cholerae bacteria. The TLC identification results showed one spot with an Rf value of 0.80 for the IFAZ-6 isolate. The chromatogram profile obtained from the TLC-Bioautography method for the IFAZ-6 isolate demonstrated antibacterial activity against bacteria that cause digestive tract infections.